Kedudukan lafaz dalam kajian usul dan pengaruhnya terhadap hukuman potong tangan - Salma, Salma (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
Understanding about punishment of stolen which is commonly heard and understood by the society is amputation of the hand. The punishment is explained clearly in the holy Quran. However, there are different interpretations about the punishment. This paper is elaborated from library research by collecting, deviding and reading many sources which appropriate with the topic and then analize the data in descriptive way. The interpretations are based on different view in usul fiqh. These differences arise from the words qat}â and yad which have more than one meaning. The meaning of the qat}â are not only as an amputation but also as hurt and anticipation. Beside that, the yad means knukles, fingers to wrist even to soldier. As a result, these differences also influence the limitation of the hand which is amputated (qat}â al-yad) in the Quran.